Neocortical spindling during wakefulness in the rat. - Hoshino, K. [UNESP]; Guimarães-Toloi, J. R. [UNESP] (My University, 1995)
Neocortical spindling that frequently occurs in rats during wakefulness was studied to evaluate the hypotheses that spindle bursts are either the electrophysiological manifestation of a short-lasting sleep episode that briefly interrupts wakefulness (due to an urge to sleep) or a short decrease of the vigilance level. In order to evaluate sleep need, the latency to the onset of natural sleep, the percentual composition of the sleep-wakefulness cycles, and the durations and intervals of desynchronized sleep episodes were determined in six male Wistar rats weighing 250-350 g and having chronically implanted electrodes for frontal electrocorticogram and cervical electromyogram. These animals were selected on the basis of spindling manifestation during wakefulness. The occurrence of spindling during a period of repeated painful tail-pinching was subsequently measured to determine the vigilance level in the same animals. Two rats were also studied during forced immobilization for the same purpose. Sleep parameters were found to be normal in all rats studied, thus excluding the hypothesis that spindling in wakefulness is a manifestation of a high sleep need. Spindling also occurred in both situations requiring a high level of vigilance (frequent tail-pinching and forced immobilization). Natural sleep cycles never started with this type of spindling, which is not related to the typical synchronization patterns of synchronized sleep. The frequency of the potentials that make up spindles in wakefulness were systematically 1 to 2 Hz lower than those of synchronized sleep in all animals studied. The possibility that spindling during wakefulness may be associated to brief episodes of distraction is discussed.